Efficiency of axenically grown Rhizoctonia solani inoculum types in evaluating sheath blight development on rice genotypes - Lore, Jagjeet S.; Jain, Jyoti; Hunjan, Mandeep S.; Kamboj, Ishwinder; Zaidi, Najam W.; Singh, Uma Shankar (Wiley, 2021)
Sheath blight caused by Rhizoctonia solani is one of the most important rice diseases worldwide, especially under irrigated agro‐ecosystem. To detect quantitative differences in disease development, three inoculum types, viz. mycelial bit, single sclerotium and mycelial ball, were evaluated against five rice genotypes using detached tiller technique. Different disease variables such as number of lesions, disease severity, vertical sheath colonization (VSC), relative vertical sheath colonization (RVSC) and mean lesion length were measured for quantification of sheath blight resistance. All the disease variables were positively correlated with each other. Among the inoculum types, mycelial ball produced significantly higher level of disease variables in all the genotypes and resolved level of resistance better than the other two methods. Significantly lower values of disease severity, VSC and RVSC were observed on rice genotype Tetep, PR 108 and D 256 as compared with susceptible check D 6766 when inoculated with different inoculum types. These results can provide a basis to design methods to evaluate quantitative sheath blight resistance with high precision in rice genotypes.